Calipar.co / Maria Maisarah Osman … [et al.] - Osman, Maria Maisarah; Erayu, Sharleyza; Ashak, Nur Azira; Mohd Kamal, Nurul Adira; Mohd Kamal, Nurul Adira (Faculty of Business and Management, 2020)
We have conducted SWOT analysis for our two competitors, Converse and Fippers. Converse is a long-running shoes product company while Fippers is a company that sells various design slippers. Both of these companies are well known and already have their own fans. Although these two companies already have loyal fans of their products, we find that there are still some weaknesses and threats in their business. However, it is common in a business where there will be strengths, weaknesses, opportunities and threats. Furthermore, under the element of key partnerships, Calipar.co has chosen Medshoe HQ as the supplier for shoes and slippers. We chose Medshoe HQ because it is one of the best shoes and slipper manufacturers in Malaysia. Calipar.co has also chosen to partner with Nova Infinity Sdn Bhd as our product packaging supplier. The design and price offered by Nova Infinity Sdn Bhd is very attractive and affordable. In addition, we chose J&T Express as the delivery service for our products to customers who purchase online. Thus, one of our key activities is our store operation at Mahkota Parade, Melaka. All our products located and sell at there and we also manage an online store. To variety our product, we also create and design new shoes. We market our product in social media to make sure our product and brand become well known in Malaysia. Additionally, under key resources we elaborate our financial sources which are consists of our own contribution, manpower plan and operational plan. As mentioned, our own contribution toward Calipar.co are RM100,000. Our company also rely to our administrative workers and suppliers. For value proposition, a great value proposition can help customers to fully understand the value of the company. By that, it helps to see what benefits them if we were able to be their choice in choosing the product. It is compulsory to understand customers’ problems in choosing materials and designing products because we want to maintain a good impression towards the customers. Next, customer relationship is good in maintaining loyalty and customer’s retention. It can enhance better service and could find new customers to purchase our product. It is a management strategy to increase the profits to our business by keeping in touch with the customers. By embracing social media is the best way to promote our business whether by making ads on Instagram or be on live on Facebook.